Effet des huiles essentielles d’eucalyptus et de menthe sur les performances zootechniques et sanitaires du poulet de chair - KASSOUS, Tahar (My University, 2022)
The aim of this work was to study the effects of essential oils (EO) of eucalyptus and mint on the growth performance and sanitary status of broiler hatched and reared under commercial conditions. The impact of these two EOs on bacterial diversity and antibiotic resistance level has also been demonstrated. This study was carried out on a total of 72,000 Cobb 500 broiler chickens distributed in 4 farms of 18,000 chickens. The first two farms are supplemented by two different commercial mixtures; the first supplemented with Mentoreef (combination of phytobiotics 1: CP1) and the second with Mentofin (CP2). The 3rd farm was considered as the positive control and the 4th was the negative control. The results of weekly changes in body weight, total body weight gain and feed conversion index obtained in this study showed that the two commercial mixtures induced an overall improvement in growth performance. The use of the CP2 combination reduced the mortality rate to 4.60% but the CP1 combination did not reduce the mortality rate. The results of this study also demonstrated that the use of the two combinations of phytobiotics has an influence on bacterial diversity, resulting in the disappearance of certain bacterial species such as Salmonella disrizonae, Citrobacter braakii and Enterobacter cloacae. In addition, a decrease in resistance and multi-drug resistance levels were observed in the enterobacteriaceae strains isolated from the group supplemented with EO and from the T- group compared to the T+ group supplemented with antibiotics. In conclusion, supplementation of eucalyptus and mint EOs could be an interesting alternative to antibiotics in improving the growth performance and the sanitary status of broiler chickens and play an important role in inhibiting certain pathogenic bacteria and reducing the rate of antibiotic resistance.
Keywords: growth, eucalyptus, essential oil, mint, menthol, antibiotic resistance, poultry